A system for monitoring training stress and recovery in high school athletes - Jeffreys, I. (Strength and Conditioning Journal, 2004)
Optimum adaptation to training requires the careful balancing of training stress and recovery. Thus it is important to be able to monitor the extent of an athlete's recovery from training bouts and to identify any symptoms of overtraining/under-recovery. This article presents a simple cost effective system of monitoring training stress in the High School or College setting, and can help the coach identify the early signs of under-recovery, allowing appropriate modifications to the athlete's program to be made.